The Role of Secondary School Teachers in Developing Cybersecurity Awareness among Its Students from the Perspective of Teachers in Private Schools in Amman - Hasweh, Rana Samir; Hamed Al-Qudah , “Mohammed Amin” (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed at identifying the role of secondary school teachers in developing students’ cybersecurity awareness in private schools in Amman. Methods: This study adopted the descriptive quantitative research method. The population of this study consisted of all secondary school teachers in Jordanian private schools during the academic year 2020/2021. A sample of (223) teachers was selected by stratified random method. Results: The results indicated that teachers rated their role in enhancing students' cybersecurity awareness as high. Statistically, no significant gender, experience in computer applications, academic qualification, or teaching experience differences in cybersecurity awareness obstacles existed. Similarly, no differences were found in teachers' awareness of cybersecurity concepts, risks, and obstacles related to specialization. Differences in awareness of cybersecurity concepts, favoring humanities subjects, were observed. Furthermore, significant differences emerged in teachers' awareness of cybersecurity concepts and risks, favoring 5-10 years of teaching experience. Similar differences were found in awareness of cybersecurity concepts, favoring a lower certificate. High estimation levels were found for activating teachers' role in increasing students' cybersecurity awareness. Finally, no statistically significant differences were observed in suggestion activation degree based on gender, specialization, computer application experience, academic qualification, or teaching experience. Conclusions: Dissemination of study suggestions to secondary school administrations and teachers as well as cooperation of various authorities to provide adequate training for teachers.